Audiobooks as educational tool in inclusive education of the visually impaired - Oliveira, Maritê de; Medeiros, Liziany Muller; Ziegler, Ana Cristina da Fonseca; Lima, Andreia Lucimar Silva de; Silva, Juliana Santos da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The school inclusion involves much more than the right to a place in an institution of regular education. It encompasses the right of the student to rely on various pedagogical alternatives, according to their specific characteristics to help in the teachinglearning process and become subject in the construction of knowledge. Thinking about the difficulties of visually impaired students being included in the regular school and as data gathered through research, it was found restricted access to literary wo rks to the visually impaired. Thus students of the Curso Técnico em Publicidade from the Instituto Estadual de Educação Visconde de Cairu, Santa Rosa, Rio Grande do Sul, formed a study group in order to find alternatives to fill this gap. Came the idea of developing talking books from the tales and children’s stories and thus was born Audiobooks Project. Throughout the project, notes, fiel d diaries were being made and were being collected materials so that each step was documented. This study discusses the development process Audiobooks Project, from its initial conception to distribution of materials to schools in the area. It is expected to provid e support for similar projects that are produced or that new pedagogical alternatives are designed, benefiting all special students and contributing to the construction of knowledge and effective citizenship.